Toward More Compassionate Healthcare Systems; Comment on "Enabling Compassionate Healthcare: Perils, Prospects and Perspectives" - Beth A. Lown (Kerman University of Medical Sciences, 2014)
Compassion is central to the purpose of medicine and the care of patients and their families. Compassionate healthcare begins with compassionate people, but cannot be consistently provided without systemic changes that enable clinicians and staff to collaborate and to care. We propose seven essential commitments to foster more compassionate healthcare organizations and systems: a commitment to compassionate leadership, to teach compassion, to value and reward compassionate care, to support clinical caregivers, to involve and partner with patients and families, to build compassion into the organization of healthcare delivery, and a commitment to deepen our understanding of compassion and its impact through research. Acting on these commitments will help us attend with care to the ill, injured, and vulnerable in every interaction.